Short-Term Effects of a Novel Eye Mask Producing Heat and Vibration for the Treatment of Meibomian Gland Dysfunction: A Pilot Study - Luca Vigo; Marco Pellegrini; Francesco Carones; Vincenzo Scorcia; Giuseppe Giannaccare (Journal of Ophthalmology)
Purpose. To investigate the short-term effects on tear film parameters and ocular symptoms of a novel eye mask producing heat and vibration developed for the treatment of dry eye disease owing to meibomian gland dysfunction (MGD). Methods. This is a pilot study including the first 20 consecutive patients (6 males, 14 females; mean age 52.4 ± 16.8 years) who were treated with a novel eye mask producing heat (42°) and vibration (up to 20 Hz) (Activa, SBS Sistemi, Turin, Italy) for 15 minutes. The treatment incorporates 2 phases in the following chronological order: 5 minutes of heating (phase I); 10 minutes of combination of heating and vibration (phase II). Noninvasive ocular surface examination was carried out before (T0) and 30 minutes after the mask session (T1) by means of Idra (SBS Sistemi, Turin, Italy) for the measurement of noninvasive break-up time (NIBUT) and lipid layer thickness (LLT). Patients’ satisfaction after treatment was ascertained by asking the patients whether they perceived improvement from their baseline symptoms according to a 5-grade scale: none = 0; trace = 1; mild = 2; moderate = 3; high = 4. Results. All patients completed regularly the mask session and no device-related adverse events were noted. NIBUT improved significantly from T0 to T1 (from 7.2 ± 1.8 s to 8.1 ± 2.1; P = 0.014). In parallel, also LLT improved from from T0 to T1 (72.5 ± 13.9 nm to 83.1 ± 16.1; P = 0.016). Seven patients (35% of the total) had a moderate satisfaction (grade 3) while 13 patients (65%) had a high satisfaction (grade 4) with treatment. Conclusions. This eye mask represents a novel well tolerated tool in the armamentarium of MGD treatments. Thirty minutes after the session, NIBUT and LLT increased significantly; furthermore, all patients reported an improvement of discomfort symptoms with a moderate to high satisfaction with treatment.